Neural responses to acute stress predict chronic stress perception in daily life over 13 months - Giglberger, Marina; Peter, Hannah L.; Henze, Gina-Isabelle; Kraus, Elisabeth; Bärtl, Christoph; Konzok, Julian; Kreuzpointner, Ludwig; Kirsch, Peter; Kudielka, Brigitte M.; Wüst, Stefan (Scientific reports, 2023)
The importance of amygdala, hippocampus, and medial prefrontal cortex (mPFC) for the integration of neural, endocrine, and affective stress processing was shown in healthy participants and patients with stress-related disorders. The present manuscript which reports on one study-arm of the LawSTRESS project, aimed at investigating the predictive value of acute stress responses in these regions for biopsychological consequences of chronic stress in daily life. The LawSTRESS project examined law students either in preparation for their first state examination (stress group [SG]) or in the mid-phase of their study program (control group [CG]) over 13 months. Ambulatory assessments comprising perceived stress measurements and the cortisol awakening response (CAR) were administered on six sampling points (t1 = − 1 year, t2 = − 3 months, t3 = − 1 week, t4 = exam, t5 =  + 1 week, t6 =  + 1 month). In a subsample of 124 participants (SG: 61; CG: 63), ScanSTRESS was applied at baseline. In the SG but not in the CG, amygdala, hippocampus, and (post-hoc analyzed) right mPFC activation changes during ScanSTRESS were significantly associated with the trajectory of perceived stress but not with the CAR. Consistent with our finding in the total LawSTRESS sample, a significant increase in perceived stress and a blunted CAR over time could be detected in the SG only. Our findings suggest that more pronounced activation decreases of amygdala, hippocampus, and mPFC in response to acute psychosocial stress at baseline were related to a more pronounced increase of stress in daily life over the following year.
Gesehen am 30.07.2024